Cross-Cultural Communication and Language Learning: Leveraging Ubiquitous Learning Platforms to Enhance Global Competency - Rizki Fauzi; Chandra Arie Widiyoko; Aries Purwanto (International Journal of Language and Ubiquitous Learning, 2026)
Background. In today’s globalized world, cross-cultural communication and language proficiency are essential for fostering international collaboration and understanding. Ubiquitous learning platforms, leveraging mobile and cloud-based technologies, have the potential to enhance language learning by providing learners with immersive, interactive, and culturally relevant experiences. These technologies bridge the gap between language learning and real-world applications, offering students opportunities to engage with authentic language use and cultural contexts. Despite their potential, the effectiveness of these platforms in promoting global competency remains underexplored. Purpose. This study aims to explore how ubiquitous learning platforms can be leveraged to improve language learning outcomes and enhance cross-cultural communication. The research examines the impact of these platforms on learners' global competency, language proficiency, and intercultural awareness. Method. A mixed-methods approach was used, combining quantitative assessments of language proficiency with qualitative interviews to understand learners' perceptions of cross-cultural communication and the role of technology in their learning experiences. Data were collected from 200 language learners across diverse cultural backgrounds. Results. The findings reveal significant improvements in language proficiency, cultural understanding, and cross-cultural communication skills. Learners reported increased engagement and motivation, with many stating that the interactive, real-world contexts provided by the platforms helped them better understand and apply language in diverse settings. Conclusion. Ubiquitous learning platforms offer a powerful tool for enhancing language learning and global competency. By integrating cultural immersion with language education, these platforms can foster more effective and meaningful language acquisition in multicultural contexts.